(untitled) (The Agriculturists, 2013)
A total of 43 (38 females and 5 males) adult native hilly chicken and 63 day-old chicks (44 hilly and 19 jungle fowl) were studied to understand their productive and reproductive performances under intensive management. The hen day egg production of hilly chicken during 11 months production period was 22.10% and average egg weight was 42.6 g. The adult body weights of female and male birds were 1701 g and 2690 g, respectively. The average daily feed consumption per bird was 101g during laying period. Hatchability of hilly chicken eggs was 91.35%. The day old chick weight of hilly chicken and jungle fowl was 29.4 g and 19.6 g, respectively (P?0.01). The body weight of hilly and jungle fowl were 503.8 g and 344.8 g, respectively, (P?0.05). There was no significant difference between hilly chicken and jungle fowl for feed consumption. Feed conversion ratios (FCR) were 2.80 and 4.4 for hilly chicken and jungle fowl, respectively (P?0.05). Mortality of adult birds during laying period was 16.4% and there was no chick mortality up to 8 weeks of age. Hilly chicken has shown potentiality to be used as meat type chicken. They require to reproduction freely under captivity to have a large number of breeding stocks for undertaking conservation and improvement programme. DOI: http://dx.doi.org/10.3329/agric.v11i2.17481 The Agriculturists 2013; 11(2) 10-13